Impact of Branding on Consumers’ Decision-Making Process in Case of Sportswear Market in Azerbaijan - Kocharli, Gulshan (ADA University, 2022)
The research topic is to analyze the impact of branding on consumers’ decision-making process in case of sportswear market in Azerbaijan. In this context, the general research objective is to explain the relationship between branding and customers’ purchasing process in sportswear market in Azerbaijan. The key concepts of research were determined as branding and customers’ purchasing process in this study. In the research, the primary data about branding and customers’ purchasing process was generated via questionnaire that was responded by 157 customers in sportswear market in Azerbaijan. There were four methods of data analysis used to analyze the relationship between branding and customers’ purchasing process in this study, which were descriptive statistics, reliability test, linear regression and independent T-test. The statistics software used to execute the data analysis process was SPSS. The key research findings presented that branding positively influenced the purchasing process of customers in sportswear market in Azerbaijan. In particular, the findings identified that each stage of customers’ purchasing process was empirically influenced by different components of branding, such as brand awareness, image, loyalty, preference and perceived quality. In this regard, the research concluded that branding was a determinant of the customers’ purchasing behavior, as it influenced customers’ problem recognition, information search, alternatives’ evaluation, purchase choice and post-purchase behavior steps of customers in sportswear market in Azerbaijan.
Keywords: Branding; Brand equity; Consumer behaviour; Sportswear market; Business